No effect of individualized sodium bicarbonate supplementation on 200-m or 400-m freestyle-swimming time-trial performance in well-trained athletes - Gurton, W. H.; Dabin, L.; Marshall, S. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This study investigated the effect of an individualized sodium bicarbonate (SB) supplementation-timing strategy on 200-m and 400-m freestyle swimming time-trial (TT) performance.